Empowering Arabic Language Learning through Community-Based Assistance: A Model from TPA Nurussajadah, Lampoko Village - Zulkiflih Zulkiflih; Fitria Fitria; Ardi Ardi; Basri Mahmud (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
The Arabic language learning mentoring program at TPA Nurussajadah aimed to enhance students' Arabic language skills and strengthen the foundations of Islamic education. This initiative employed various interactive approaches, including language games, simulations, and interactive dialogues, which actively engaged students in the learning process. Additionally, the program provided intensive training for teachers, equipping them with modern and effective teaching methods tailored to young learners. The results were promising, showing a significant improvement in students' understanding of Arabic, with an average score increase of 30% compared to their initial assessments. Teacher competence also saw notable enhancements, allowing for more confident and effective instruction. Parental involvement was another key achievement, as parents became more engaged in their children's educational journey, reinforcing the importance of learning Arabic at home. The program's success highlights the effectiveness of interactive and immersive teaching strategies combined with comprehensive teacher training in improving students' language skills and supporting Islamic education. However, to ensure the program's sustainability, ongoing efforts are needed to address challenges such as limited facilities, inadequate teaching resources, and the varying levels of student proficiency. These issues require strategic planning and community support to maintain and build upon the program's successes.